2020
DOI: 10.1017/s1047951120002474
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic study in children with osteogenesis imperfecta

Abstract: Background: Osteogenesis imperfecta is a collagen type I bone disorder. Recently, extra-skeletal manifestations have been described, including many cardiovascular alterations. This study aims to report echocardiogram study in children with osteogenesis imperfecta compared to a control group. Methods: A cross-sectional comparative study took place in the Reference Center for Treatment of Osteogenesis Imperfecta in Southern Brazil. Fifty-four patients with osteogenesis imperfecta were pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In this study, we found OI children had significant higher percentage of mild mitral or triple valve regurgitation than control group, which was worthy of a long-term follow-up. We did not find moderate to severe valvular prolapse or regurgitation in this OI cohort, which was consistent with other studies in OI children ( 33 ). This difference of detection rate of valvular abnormalities between OI children and adults indicated that cardiovascular diseases might develop with aging in OI patients, so it was necessary to evaluate the cardiovascular structure and function of OI patients during the long-term follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, we found OI children had significant higher percentage of mild mitral or triple valve regurgitation than control group, which was worthy of a long-term follow-up. We did not find moderate to severe valvular prolapse or regurgitation in this OI cohort, which was consistent with other studies in OI children ( 33 ). This difference of detection rate of valvular abnormalities between OI children and adults indicated that cardiovascular diseases might develop with aging in OI patients, so it was necessary to evaluate the cardiovascular structure and function of OI patients during the long-term follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…In a small sample study, OI children were found to have greater dimensions of the main aorta and LVEDd than control group, but without significant change in heart function ( 31 ). Compare with control group, OI children exhibited larger LV internal dimensions and dilated main pulmonary arteries ( 32 , 33 ). Our study confirmed the alterations of heart and aorta in OI children, including larger internal diameters of MPA and left heart chambers, with lower LVEF than BSA-matched healthy children.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Few records of conditions unrelated to hearing loss were identified ( n = 2). Most records included adults [ 13 , 29 , 31 , 89 , 90 , 93 , 96 , 101 , 106 , 111 , 115 , 116 , 122 , 123 , 190 , 212 , 215 219 ] Cardiovascular 15 Records provided clinical heart measurements ( n = 11) and information on valvular disease ( n = 8), while heart failure ( n = 2), hypertension ( n = 3) and atrial fibrillation ( n = 1) were not well-described [ 13 , 29 , 139 , 142 , 151 , 170 , 175 , 182 184 , 220 – 224 ] Pulmonary 11 Four records described breathing problems and respiratory disease. Few data on wheezing ( n = 2) and respiratory arrest ( n = 1) were identified.…”
Section: Resultsmentioning
confidence: 99%